(untitled) (Lebenswelt. Aesthetics and philosophy of experience., 2014)
The knowledge about the cerebral basis of reinforce and about the conditionings that structure motivations, believing and desires should not overshadow the fact that one of the characteristics of the desire is to be concatenated with a series of experiences, beliefs and points of view hardly reducible to single entities, with their own autonomy. It is possible to characterize the single desire, believing, intention only in the field of a wider net of attitudes that provides a certain coherence to every single intention, desire, memory or perception, or that points to an internal logic, precisely that which reveals that every single attitude cannot be separated from the subtle and wide net of attitudes that an individual has formed, good or bad, in his life.